Aplikasi Sistem Informasi Geografis dan Penginderaan Jauh untuk Pemetaan Penggunaan dan Kesesuaian Lahan di Desa Batur Tengah Kabupaten Bangli - ANDREY ANTASARI RANGKUTI; INDAYATI LANYA; R. SUYARTO (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Application of Geograpic Information System and Remote Sensing for Mapping of Land Use and Suitability ini Batur Tengah Village Bangli This study aims to map land use and evaluate the suitability of land for horticultural, secondary and plantation crops. This research held from December2017 - March 2018 using a method consisting of, identification of satellite images (land use), field surveys, reinterpretation of land use maps, analysis of soil samples and land suitability classification. The results that there were eight types of land use in Batur Tengah Village with a total area of 474 ha. The actual class of land suitability of fruit horticulture plants is generally S3 (marginal suitability) with dry season limiting factor, soil texture, soil-CEC and N-total and slope, potential suitability class S3. The actual land suitability class of plantation (coffee) plants is generally S3 with a dry season limiting factor, soil texture, soil-CEC, N-total and slope. Potential land suitability class S3. The class of actual land suitability of vegetable horticulture plants is generally S3 (marginal suitability) with dry season limiting factors, soil texture, soil-CEC and N-total and slope, potential land suitability class S3. The actual land suitability class of palawija crops is generally N (not suitable) with dry season limiting factors, soil texture, soil-CEC and N-total and slope, potential land suitability class S3. The land suitability geographic information system is presented interactively which can display land suitability classes, agricultural commodities and land use types.